2012
DOI: 10.1093/annonc/mdr036
|View full text |Cite
|
Sign up to set email alerts
|

The impact of phosphorylated AMP-activated protein kinase expression on lung cancer survival

Abstract: High pAMPK expression levels are associated with increased survival in patients with NSCLC, especially those with ADC. Our results support further evaluation of AMP-activated protein kinase as a potential prognostic and therapeutic target for lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 29 publications
6
53
0
Order By: Relevance
“…These findings are consistent with previous studies that inactivating mutations of LKB1 are seen more frequently in smokers and poorly differentiated NSCLC tumors (Matsumoto et al, 2007) and are associated with a shorter latency, more frequent metastasis, and accelerated pulmonary tumorigenesis (Ji et al, 2007). Recently, William et al found that pAMPK expression levels were significantly higher in never smokers versus former smokers versus current smokers in surgically resected NSCLC (William et al, 2012). A positive pAMPK expression was associated with increased overall survival (OS) and recurrence-free survival (RFS) (William et al, 2012).…”
Section: Expression Of Proteins In the Ampk Pathwaysupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are consistent with previous studies that inactivating mutations of LKB1 are seen more frequently in smokers and poorly differentiated NSCLC tumors (Matsumoto et al, 2007) and are associated with a shorter latency, more frequent metastasis, and accelerated pulmonary tumorigenesis (Ji et al, 2007). Recently, William et al found that pAMPK expression levels were significantly higher in never smokers versus former smokers versus current smokers in surgically resected NSCLC (William et al, 2012). A positive pAMPK expression was associated with increased overall survival (OS) and recurrence-free survival (RFS) (William et al, 2012).…”
Section: Expression Of Proteins In the Ampk Pathwaysupporting
confidence: 91%
“…Recently, William et al found that pAMPK expression levels were significantly higher in never smokers versus former smokers versus current smokers in surgically resected NSCLC (William et al, 2012). A positive pAMPK expression was associated with increased overall survival (OS) and recurrence-free survival (RFS) (William et al, 2012). And OS and RFS were statistically superior in pAMPK-positive than in pAMPK-negative patients with adenocarcinoma (median OS: 5.6 and 4.2 years, median RFS: 5.0 and 2.4 years, respectively), whereas they were similar in those patients with squamous cell carcinoma (William et al, 2012).…”
Section: Expression Of Proteins In the Ampk Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have focused on the clinical significance of tumor pAMPK or MAPK3/1 expression in predicting the outcome of solid tumors. Tumor pAMPK expression has also been reported to be a significant marker for increased survival independent of conventional clinicopathological factors in colorectal and lung cancer [11,16]. However, data on the relationship between the expression of these genes and the clinical outcome of gastric cancer have not yet been published.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, clinical studies have shown that an increased expression of AMP/phosphorylated AMPK (pAMPK) or MAPK3/1 is associated with the tumor grade and prognosis for various solid tumors, including colorectal, ovary, breast, prostate and cervical cancer [11,12,13,14,15]. For example, William et al [16] reported a correlation between high expression of pAMPK, as a surrogate marker for activated AMPK, and a better prognosis for patients with non-small cell lung cancer. However, no published study has yet investigated possible associations between the expression of pAMPK, NUAK2, MAPK3/1 and PDK-1 and the clinical outcome of resected gastric cancer.…”
Section: Introductionmentioning
confidence: 99%